Rancang Bangunsistem Informasi Program Acara Televisi Sebagai Sarana Media Informasi Berbasis Web (Studi Kasus Banyumas Televisi Purwokerto) - Agung Baitul Hikmah - AMIK BSI Purwokerto (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract   Television industry business is very excited in Indonesia because this supports nearly 80% Indonesia people who always watch TV in front of that until many hours.In Indonesia Television Industry is reaching not only National television but also government television or private television. Based on the data in 2004 it said that local television in Indonesia has reached more than 200 television . The number of these are still growing together with opening for permited counter in all of the villages, so that it supports to grow up the competitions especially local television in giving information the television schedule programmes to the audiences, for example internet media based on website as information media. In this case,Banyumas television (BMSTV) is one of local television which made in Banyumas people which is not yet to have website facilities to show information either schedule programmes, activities or another programmes which are accurate and fast for the audiences. Looking at this conditions, so we must need  useful solutions to solve the problem so the information can be accepted directly by dhe public within internet media based on website.in designing an information system uses waterfall method which consists of several stages including Requirement Analysis and Definition,System and Software Design,Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. It hoped information system which is designed can help audiences/publics in getting acces for information of television programsaccurately and quickly so that the audieces/publics are not difficult to find out television programmes especially which is showed by Banyumas television (BMSTV) because it can find out directly  based Internetmediawebsites.   Keyword: Television Programs, Information Systems, Website